Determinação do teor alcoólico de vodcas: uma abordagem multidisciplinar no ensino da física, química e matemática - Vaz, Ednilson Luiz Silva; Monteiro, Marco Aurélio Alvarenga [UNESP]; Monteiro, Isabel Cristina de Castro [UNESP]; Acciari, Heloísa Andréa [UNESP]; Codaro, Eduardo Norberto [UNESP] (My University, 2013)
In this paper, it is proposed an experimental activity to be developed with high school students, addressing the concepts of density and surface tension from a multidisciplinary approach among Physics, Chemistry and Mathematics. In this proposal, students are challenged to determine the alcohol content of vodkas from intensive physical properties of liquids. Two calibration curves were obtained, one for density and another for surface tension as a function of ethanol concentration in water. The alcohol levels obtained from these properties were very close to the values given by manufacturers, due the similarity of these beverages with ethanol-water binary mixtures.

Neste trabalho, propõe-se uma atividade experimental para ser desenvolvida com alunos do ensino médio, abordando os conceitos de densidade e tensão superficial a partir de uma abordagem multidisciplinar entre a física, química e matemática. Nessa proposta, os alunos são desafiados a determinar o teor alcoólico de vodcas a partir das propriedades físicas intensivas dos líquidos. Foram obtidas duas curvas de calibração, uma de densidade e outra de tensão superficial, em função da concentração de etanol em água. Os teores alcoólicos obtidos a partir dessas propriedades foram muito próximos dos valores fornecidos pelos fabricantes, fato atribuído à semelhança dessas bebidas com as misturas binárias etanol-água.
Determination of alcoholic content in vodkas: a multidisciplinary approach in teaching of physics, chemistry and mathematics
Keywords: Density; Surface tension; Vodka; Densidade; Tensão superficial; Vodca